2016
DOI: 10.3311/ppch.8869
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of TiO2 Nanoparticles on the Aquatic Ecosystem: A Comparative Ecotoxicity Study with Test Organisms of Different Trophic Levels

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 45 publications
(52 reference statements)
0
6
0
Order By: Relevance
“…The susceptibility values of P. subcapitata towards NPs in terms of LC50 (Lethal Concentration, 50%) were found to be 0.19 mg/L (n-Ag), 0.54 mg/L (n-Cu), 8.30 mg/L (n-Al), and 0.35 mg/L (n-Ni), and it was confirmed that P. subcapitata was the most sensitive organism to Ni NPs. Fekete-Kertész et al [ 45 ] showed a 32–50% inhibition of P. subcapitata when organisms were treated with 3.13–25 mg/L TiO 2 NP concentrations, and a greater NP toxicity effect caused by high NP concentration of 50 mg/L. The effect of two TiO 2 NPs (anatase and rutile) on the growth of P. subcapitata using different exposure systems was reported by Manier et al [ 46 ].…”
Section: Resultsmentioning
confidence: 88%
“…The susceptibility values of P. subcapitata towards NPs in terms of LC50 (Lethal Concentration, 50%) were found to be 0.19 mg/L (n-Ag), 0.54 mg/L (n-Cu), 8.30 mg/L (n-Al), and 0.35 mg/L (n-Ni), and it was confirmed that P. subcapitata was the most sensitive organism to Ni NPs. Fekete-Kertész et al [ 45 ] showed a 32–50% inhibition of P. subcapitata when organisms were treated with 3.13–25 mg/L TiO 2 NP concentrations, and a greater NP toxicity effect caused by high NP concentration of 50 mg/L. The effect of two TiO 2 NPs (anatase and rutile) on the growth of P. subcapitata using different exposure systems was reported by Manier et al [ 46 ].…”
Section: Resultsmentioning
confidence: 88%
“…Assessing ecotoxicity of TiO 2 -NPs against bioluminescent bacterium (Aliivibrio fischeri), algae (Pseudokirchneriella subcapitata, Scenedesmus subspicatus, and Chlorella vulgaris), protozoon (Tetrahymena pyriformis), water flea (Daphnia magna), and an aquatic macrophyte, Lemna minor [29] revealed these organisms showed significant behavioral and physiological changes when exposed to low TiO 2 -NP concentrations (0.1 and 0.05 μg/L), thus demonstrated the ability of TiO 2 -NPs to alter molecular pathways via which these organisms obtained vital nutrition for growth and synthesis of compounds (i.e., chlorophyll, etc. ).…”
Section: Titanium Dioxide Nanoparticlesmentioning
confidence: 99%
“…Previous studies have revealed that treatments with 12.5, 25, and 50 mg/L nTiO 2 decreased the growth rate of Chlorella vulgaris by 33%, 36%, and 49%, respectively (Fekete‐Kertész, Maros, Gruiz, & Molnár, 2016). Chronic exposure to 1.78 mg/L nTiO 2 resulted in the collapse of Daphnia magna populations after five generations (Jacobasch et al, 2014).…”
Section: Introductionmentioning
confidence: 97%